The military and society in Iraqbarracks, soldiery, parallel army (Journal of Imam Al-Kadhim College, 2025)
The Iraqi army has gone through a number of phases, reflecting the successive historical cycles of the army's rise and fall. During its rise, the relationship between the military and society, and its heightened symbolism, were the same factors that weakened it and prompted the search for an ideological army as an alternative to defend power. The stages that accompanied the Iraqi army since its founding are represented by the "barracks" phase, its isolation from society, characterized by its unique values and customs, allowing it to be an independent institution with the necessary capabilities. However, the rise of the military's symbolism and the accompanying political circumstances pushed the army to leave the barracks. This departure was motivated by expanding its role to include political and developmental issues. There were two paths to working outside the barracks: one expanded into society without departing from the context of the political system's institutions, influencing society and enabling interaction to strengthen its presence within the sphere of control of state institutions. The second is its entry into the phase of parallel armies with society, which was evidence of the political regime's recognition of the weakness of the official army, or lack of trust in it. This resulted in the rise of a parallel army based on a doctrinal ideology that emerged from society. Here, state institutions were unable to control or curb the expansion and power of these parallel armies or regulate their behavior towards the regime or society. This is the most dangerous phase in the army's expansion towards society.
Keywords: army; parallel army; military symbolism; soldiering; military; army, parallel army, military symbolism, soldiering, military